Neck Circumference as A Screening Tool for Obesity in Pre- and Primary School Children in Puducherry India – A Cross-Sectional Study - Nair, Gayathri G; Ashok, Umayorubhagom; Prashant, Dhongadi; Jayaseelan, Ooviya (National Journal of Community Medicine, 2024)
Introduction: Obesity has become the 21st Century’s greatest challenge and threat. Around 50% of the obese children become obese adolescents, of which 80% become obese adults. Methodology: Cross-sectional analytical study was done on 930 pre- and primary school children. Neck circumference, weight, height, waist and hip circumference was recorded. Overweight/obese identified according to WHO standards. Age-specific percentile charts for boys and girls were drawn with data from the apparently normal children in the study population. Results: The Neck Circumference measurements ranged from 23.64(±1.16) to 28.49(±2.87) in boys and 23.59(±1.63) to 27.6(±2.67) in girls. ROC analysis derived cut-offs for overweight and obesity in each age group/gender were found to have high sensitivity (80-100%) and specificity (60-95.9%). Using the reference percentile data/curves, and the cut –offs obtained by ROC analysis, a neck circumference above the 75th percentile for age and gender can be regarded as overweight and above the 90th percentile as obese in both boys and girls. Conclusion: The study concludes that the Neck circumference is a valid and effective screening tool for overweight/obesity in pre and primary school children.